The Educational Choice of Working Women - Feidjel, zahra; ketfi, azouz (Journal of Social Sciences and Humanities, 2024)
The current study aims to identify the educational choice of working woman according to each of the age variables, type of profession, the college. And knowing the extent to which various factors are taken into account in choosing specializations, especially for female students as future workers. The study was applied to sample of 101 female employees at the Faculty of Economics, Commercial and Management Sciences and the Faculty of Technology- M'sila University, who were chosen randomly. The study relied on the descriptive method, the statistical methods were limited to One-Way analysis of variance and two independent Samples t-test. The results of the study found the following: - no differences in the educational choice of working woman due to the difference in the variable age. - no differences in the educational choice of working woman due to the difference in the variable type of profession. - no differences in the educational choice of working woman due to the difference in the variable college.